2021
DOI: 10.1177/09721509211037209
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Human Resource Management Practices, Knowledge Management Practices, and Performance: Evidence from the Healthcare Industry in India

Abstract: The objective of the present study is to examine the impact of human resource management (HRM) practices on organizational performance. Knowledge management (KM) practices as a moderator in the relationship between HRM practices and organizational performance are studied by developing a conceptual model. Using a structured survey instrument, the data were collected from 979 employees from 10 hospitals in the southern part of India (Tiruchirappalli District of Tamil Nadu). After thoroughly checking the instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Besides, Ohanyere et al (2021) demonstrated the synonymous finding with previous researchers regarding training practices and organizational performance among employees in Nigeria. In contrast, the Parayitam et al (2021) finding shows that training and development practice and organizational performance are not connected. Researchers expressed that performance could be hindered if insufficient training and development opportunities exist.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Besides, Ohanyere et al (2021) demonstrated the synonymous finding with previous researchers regarding training practices and organizational performance among employees in Nigeria. In contrast, the Parayitam et al (2021) finding shows that training and development practice and organizational performance are not connected. Researchers expressed that performance could be hindered if insufficient training and development opportunities exist.…”
Section: Literature Reviewmentioning
confidence: 86%
“…In industrial–organisational psychology and human resource management (HRM), the link between organisational practices of training and development, compensation and employee attitudes has been widely studied (Brayfield & Crockett, 1955; Büssing et al, 1999; Fairbrother & Warn, 2003; Kampkötter, 2017; Uraon, 2018; Van Beurden et al, 2021). Human resource management (HRM) practices primarily aim to motivate employees for higher performance (DeNisi & Smith, 2014; Parayitam et al, 2021; Selvarajan & Cloninger, 2012). Research on the implications of career planning, training and development, performance appraisal and compensation in organisations has been documented (Aruldoss et al, 2022; Lee & Bruvold, 2003; Lumley et al, 2011; Poon, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, challenges and obstacles can be handled with the strategic use of HRM practices. Various studies investigated the nexus between HRM practices and performance in various organizational contexts in India (Darwish et al, 2020; Kundu & Gahlawat, 2018; Parayitam et al, 2021). However, there is a dearth of studies investigating the role of HRM practices on the different non-financial aspects of organizational performance in India, particularly in the banking industry.…”
Section: Introductionmentioning
confidence: 99%